SAPOR-s system for automatic programming of NC machines and systems - Gatalo, Ratko; Hodolič, Janko; Borojev, Ljubomir; Zeljković, Milan; Klarić, Rade; Zeljković, Željko (Journal of Production Engineering, 1993)
This paper represents an integral review of previous results in the development of the SAPOR-S system for automated design of control information and data media for machining rotational parts on an NC turning machine. SAPOR-S presents an original solution both in its fundamental concept and in the design of some of its modules. During its development, the system was designed to run on various computer systems. The second part of the paper reviews the current status of the system’s development. It begins with the system’s model and concept and then provides an overview of the characteristics of certain subsystems, including the input (source) information initialization, system processor, system post-processor, and information database. The section concludes with a case study demonstrating the application of the system in generating control information. In the third part, the paper outlines potential directions for the system’s future development. It discusses the fundamental directions for the further advancement of the SAPOR-S system, along with the results achieved in this area so far.